Effects of outdoor education on group cohesion among second year undergraduate teacher trainee from selected teacher education institutes in Malaysia - Mohd Yasim, Mazuki (2016)
The study seeks to investigate the effect of outdoor education camp toward group cohesion on the second year undergraduate teacher trainees from selected Teacher Education Institutes of Malaysia. It also examines the socio-demographic influences and sequence of activity that encourage group cohesion improvement. The study also attempts to shed light upon the delayed effect after two months completion of the camp. A pre-test and posttest approach with non-equivalent control group was utilised among 350 second year undergraduate students from four selected Teacher Education Institutes of Malaysia.Meanwhile, there is no control group used for the delayed post-test. A modified version of Group Environment Questionnaire (GEQ) and open ended questionnaire were used to gather data from pre,post and delayed post-test. Results from MANCOVA procedures suggested that the camp had positively improved the experimental group‟s group cohesion.Previous experience, place of residence, gender and camp location were found to have significant influence on the improvement of group cohesion.However, the study also revealed that this gain diminished over thetwo month period as measured by the delayed post-test. Responses from teacher trainees found that sequence of activity from low to high risk activity is the appropriate and influenced students‟ group cohesion improvement.